Case examples in child welfare and family services for social workers - Cheng, Tyrone (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book provides social work students at both undergraduate and graduate level with compelling child welfare case examples, intervention plans, and tips for building working alliances with clients. Using the instruction/practice sheets that illustrate sound approaches for joining with clients to tailor their own interventions, students are provided with the tools to work out the application of assessment and intervention strategies with regard to the particular circumstances of each example. Throughout, the emphasis is on growing the working alliance between social worker and client, reflecting the strength perspective emphasized in social work practice"--
Keywords: Child welfare; Social service; SOCIAL SCIENCE / Human Services